THE FACTS ABOUT PENICILLIN ALLERGY: A REVIEW - Sanjib Bhattacharya (Wolters Kluwer Medknow Publications, 2010)
Hypersensitivity reactions are the major problem in the use of penicillins. Truepenicillin allergy is rare with the estimated frequency of anaphylaxis at 1-5 per 10 000cases of penicillin therapy. Hypersensitivity is however, its most important adversereaction resulting in nausea, vomiting, pruritus, urticaria, wheezing, laryngeal oedemaand ultimately, cardiovascular collapse. Identification of patients who erroneously carryß-lactam allergy leads to improved utilization of antibiotics and slows the spread ofmultiple drug-resistant bacteria. Cross-reactivity between penicillin and second and thirdgeneration cephalosporin is low and may be lower than the cross-reactivity betweenpenicillin and unrelated antibiotics.